2013
DOI: 10.18869/acadpub.3dj.1.2.24
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Developmental and Acquired Dental Anomalies on Digital panoramic Radiography in Patients Attending the Dental Faculty of Rasht, Iran

Abstract: Introduction: Many epidemiological studies have been conducted to determine the prevalence of the various types of the dental anomalies. The aim of the present study was determination of developmental and acquired dental anomalies in patients attending the faculty of dentistry in Rasht, Iran. Materials and Methods: In this retrospective cross-sectional study, 1224 digital panoramic radiographs belong to 758 females and 466 males were assessed for evaluation of 10 developmental and acquired dental anomalies. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
5
3

Year Published

2014
2014
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 18 publications
1
5
3
Order By: Relevance
“…By contrast, Saberi et al [21] reported a prevalence of tooth impaction of 3.41%. A prevalence of impaction of 16.6% was reported by Dalili et al [4], 8.3% by Ezoddini et al [7], and 2.95% by Ghabanchi et al [8] in different regions of Iran [21]; these values are much lower than those in our study. This inconsistency may have arisen because third molars were not counted as impacted teeth in the previous studies, but they were counted in our study.…”
Section: Discussioncontrasting
confidence: 77%
“…By contrast, Saberi et al [21] reported a prevalence of tooth impaction of 3.41%. A prevalence of impaction of 16.6% was reported by Dalili et al [4], 8.3% by Ezoddini et al [7], and 2.95% by Ghabanchi et al [8] in different regions of Iran [21]; these values are much lower than those in our study. This inconsistency may have arisen because third molars were not counted as impacted teeth in the previous studies, but they were counted in our study.…”
Section: Discussioncontrasting
confidence: 77%
“…The most prevalent teeth with dilacerations were the maxillary second premolar and lateral incisor. The prevalence of dilacerations was reported to be 15% by Ezoddini et al, 16 1.44% by Ghabanchi et al, 19 and 5.6% by Dalili et al 18 This inconsistency might be attributed to the settings of these studies as well as the accuracy of the methods and the diagnostic criteria that were used.…”
Section: Discussionmentioning
confidence: 95%
“…Dalili et al,18 Ezoddini et al,16 and Ghabanchi et al19 reported the prevalence of impaction to be 16.6%, 8.3%, and 2.95% in different regions of Iran. This inconsistency might originate from the lack of third molar impaction.…”
Section: Discussionmentioning
confidence: 98%
“…As previously discussed, the majority of studies done by investigators around the world have shown numerous variations [2,4,5,12,[19][20][21]. A plausible explanation for these observations may be due to differences in study design, diagnostic criteria, sampling techniques, racial differences, influences of environmental factors, and the effect of nutritional status on tooth development [6].…”
Section: Discussionmentioning
confidence: 99%